Micropropagation and Genetic Fidelity of Fegra Fig (Ficus palmata Forssk.) and Grafting Compatibility of the Regenerated Plants with Ficus carica - Ahmed Ali Al-Aizari; Yaser Hassan Dewir; Abdel-Halim Ghazy; Abdullah Al-Doss; Rashid Sultan Al-Obeed (Plants, 2024)
Ficus palmata is an important fig species that produces edible and nutritious fruit and possesses several therapeutic uses. This study reports an effective method for the micropropagation of F. palmata using nodal explants. In vitro shoots were cultured for 7 weeks onto MS medium fortified with different concentrations of cytokinins, light intensities, sucrose concentrations, and light/dark incubation treatments. Optimal axillary shoot proliferation (10.9 shoots per explant) was obtained on a medium containing 30 g/L sucrose and supplemented with 2 mg/L 6-benzylaminopurine (BAP) under 35 μmol/m2/s light intensity. Dark incubation limited the foliage growth but favored shoot elongation and rooting compared with light incubation. Elongated shoots, under dark conditions, were rooted (100%; 6.67 roots per explant) onto MS medium containing 1 mg/L indole-3-acetic acid (IAA) and 1.5 g/L activated charcoal. The micropropagated plantlets were acclimatized with a 95% survival rate. In this study, the genetic fidelity of micropropagated F. palmata clones along with their mother plant was tested using randomly amplified polymorphic DNA (RAPD), inter-simple sequence repeats (ISSR), and start codon targeted (SCoT) molecular markers. The genetic similarity between the micropropagated plantlets and the mother plant of F. palmata was nearly 95.9%, assuring high uniformity and true-to-type regenerated plants. Using micropropagated F. palmata plantlets as a rootstock proved appropriate for the grafting F. carica ‘Brown Turkey’. These findings contribute to the commercial propagation and production of the fig crop.